On-Station Green Manure Cover Crop (GMCC) Intercropping Strategy Trial under Conservation Agriculture - International Maize and Wheat Improvement Center; Zambian Agriculture Research Institute (International Food Policy Research Institute, 2019)
This study contains data originated from on-station trials that were conducted to evaluate the performance of green manure cover crops on crop productivity, and soil quality and residual effects. These trials were conducted at Msekera Research Station in Zambia. The following treatments were used. - Maize ? sole cropping; - Maize ? Pigeonpea intercropping; - Lablab ? sole cropping (in rotation with maize in year 2); - Maize ? lablab intercropping planted at the same time as maize; - Maize ? lablab intercropping planted 1 week later than maize; - Maize ? lablab intercropping planted 3 weeks after the maize; - Cowpea - sole cropping (in rotation with maize in year 2); - Maize - Cowpea intercropping planted at the same time as maize; The following were used as sub-treatments. - No fertilizer addition; - Application of 100kg ha-1 Compound D (10:20:10).